2001
DOI: 10.1038/sj.onc.1204513
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression changes induced by HTLV-1 Tax: evidence for MLK-3 mixed lineage kinase involvement in Tax-mediated NF-κB activation

Abstract: The Tax protein of human T-lymphotropic virus type 1 (HTLV-1), an oncoprotein that transactivates viral and cellular genes, plays a key role in HTLV-1 replication and pathogenesis. We used cDNA microarrays to examine Tax-mediated transcriptional changes in the human Jurkat T-cell lines JPX-9 and JPX-M which express Tax and Tax-mutant protein, respectively, under the control of an inducible promoter. Approximately 300 of the over 2000 genes examined were di erentially expressed in the presence of Tax. These gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 72 publications
4
78
0
Order By: Relevance
“…The most notable viral regulatory protein is, however, the 40 kDa transactivator protein Tax (Jeang, 2001;Yoshida, 2001;Franchini et al, 2003). In addition to regulating viral gene expression through the 5 0 long terminal repeat (LTR), Tax induces or represses the expression of a large variety of cellular genes (Sun and Ballard, 1999;Ng et al, 2001). Consistently, emerging evidence suggests that Tax serves as the primary oncogenic mediator of HTLV-I (Franchini et al, 2003).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The most notable viral regulatory protein is, however, the 40 kDa transactivator protein Tax (Jeang, 2001;Yoshida, 2001;Franchini et al, 2003). In addition to regulating viral gene expression through the 5 0 long terminal repeat (LTR), Tax induces or represses the expression of a large variety of cellular genes (Sun and Ballard, 1999;Ng et al, 2001). Consistently, emerging evidence suggests that Tax serves as the primary oncogenic mediator of HTLV-I (Franchini et al, 2003).…”
Section: Introductionmentioning
confidence: 69%
“…One example is the mixed-lineage kinase 3 (MLK-3) (Ng et al, 2001), a member of the MAP3K family with a known function in NF-kB activation (Hehner et al, 2000). At least under overexpression conditions, MLK-3 dominant-negative mutants inhibit Tax-stimulated NF-kB activation.…”
Section: Indirect Mechanisms Of Nf-jb Activation By Htlv-i: Involvemementioning
confidence: 99%
“…These changes include several factors with growth promoting and/or antiapoptotic functions whose expression patterns are modulated by Tax (Ng et al, 2001). Below, we summarize some salient examples (Figure 1).…”
Section: Stimulation Of Cell Growth Through Signal Transductionmentioning
confidence: 99%
“…The DNA dependent protein kinase complex (DNA-PK) assembles from three distinct subunits, Ku70, Ku80 and the DNA-PK catalytic subunit and is thought to be the sensor and regulator element of DSB repair. Gene array studies revealed that Tax expressing cells display reduced levels of Ku80 mRNA as compared to controls (Ng et al, 2001), which could reduce the efficiency of DSB repair leading to an increased genomic mutation frequency. More studies will be needed to test this possibility.…”
Section: Effect Of Tax On Cellular Dna Repairmentioning
confidence: 99%